Antithrombin deficiency: A pediatric disorder. Issue 202 (June 2021) - Smith, Natalie; Warren, Beth Boulden; Smith, Julie; Jacobson, Linda; Armstrong, Jennifer; Kim, Jihye; Di Paola, Jorge; Manco-Johnson, Marilyn
Abstract: Introduction: Hereditary antithrombin (AT) deficiency is an autosomal dominant thrombophilic disorder. Guidelines do not support routine testing of children based on personal or familial thrombosis. Aim: To investigate clinical, genetic and laboratory profiles of AT deficient children and their affected family members. Materials and methods: Data were analyzed from a prospective cohort of pediatric patients with AT deficiency. The SERPINC1 gene was sequenced for all individuals with available DNA. AT, thromboelastography (TEG), calibrated automated thrombogram (CAT), D-dimer, thrombin-antithrombin complex (TAT) and factor VIII activity were performed on patient samples. Results: Thirty-six individuals from 11 families had AT deficiency (activities 45–70 U/dL) with incident thrombosis in 13 children and 10 adults (64% overall). Three neonates presented with middle cerebral artery and/or aortic occlusions with inferior vena cava and cerebral or renal vein thromboses in 2 of the 3. Two pre-pubertal children were symptomatic, one with cerebral venous sinus thrombosis who suffered recurrent arterial and venous thrombi. Both Type I and Type II AT deficiencies conferred a high severity of thromboses. Heterozygous SERPINC1 mutations were identified in seven families; three were novel, resulting in missense, splice site and frameshift alterations. Thrombin generation (CAT) was increased in all asymptomatic affected patients including 9 children and 1 adult. Conclusions: Genetic AT deficiency often presents in infants and children, warranting laboratory evaluation based on personal and family history. Increased thrombin generation was detected in all asymptomatic children and adults, suggesting a possible role in detecting and monitoring individuals at risk for thrombosis. Highlights: Antithrombin deficiency commonly presents in pediatric patients, including in utero and perinatal thromboses. Families with null mutations suffered more unusual and serious thromboses compared with type II mutations. Asymptomatic persons with antithrombin deficiency demonstrate increased thrombin generation, a potential tool to identify and monitor thrombotic risk. Centers of excellence in Thrombosis and Thrombophilia are important to integrate clinical and research aspects of investigation and care.